Exploring Teacher’s Perspective on the Use of Games in English Language Learning at SMPN 1 Waru - Azizah, Qonitah; Madjid, Hilda Izzati; Lukmansono, Toto (ICONELT, 2024)
This study aims to find out teachers’ perspectives on using games in English learning at SMPN 1 Waru, Sidoarjo. Using a descriptive qualitative design, the data collected from questionnaires and interviews of the 7th-grade English teachers are analyzed. The findings of this study show that the teachers view that the use of games in English learning can give a new learning impression to students because the presence of the game can affect their learning style. The presence of games in the midst of English language learning can address the misconception that language acquisition is primarily based on reading textbooks. Of course, some challenges have also been felt, such as the presence of games for the first time in the midst of learning English gives a sense of lack of excitement when students are first introduced to one type of game, but over time, there must be a competitive spirit and a great sense of enthusiasm. In addition, some problems, such as using digital games and the need for strict supervision during running language games, so as not to become a boomerang for the teacher.